Programming in C++ lessons and applications - D'Orazio, T. B. (Mcraw Hill Education, 2009)
Focuses on developing programs for solving engineering and science problems. Each chapter of this book is divided into two parts - lessons and application examples. The lessons teach C++ language elements and simple programming techniques, and the application programs teach engineering program design.